Identification of industries with potential in employment generation through the estimation of production chains and employment – output elasticities - Sánchez Gómez, Manuel Esteban (2021)
This paper presents indexes of production linkages and employment-output elasticities for the Costa Rican economy with data from the Input Output Table of 2012. The estimation of the indexes follows the methodology of Chenery and Watanabe (1958), while the elasticity coefficients were calculated following Valadkhani (2003). It was found that the industries with higher linkages are: livestock farming, agricultural support services, storage services, construction, financial activities and telecommunication industry; meanwhile the industries with highest employment output elasticities are: retail trade, education and construction. By fiscal regime, it is noted that firms in free trade zones tends to be more inelastic in terms of their contribution to total employment when their demand increases.